Access control system using palm of the hand image processing (2013)
In this article is presented the design of a biometric system for the palm of the hand, oriented to offer a people access control, without the typical drawbacks of this system, like the no carrying of the budge, erase of the id barcode, unreadable fingerprints, dirty or soiled hands. The system uses a cubicle with a guide to position the palm of the hand and a constant lighting system. With a camera is acquired the back of the hands' image and is processed with MATLAB to get measurements like skin color, width and hand length, to use parametrical non parametric classifier and to identify the palm of the hand of one or other users.